Effects of acute insulin‐induced hypoglycaemia on endothelial microparticles in adults with and without type 2 diabetes. Issue 3 (30th October 2018) - Al‐Qaissi, Ahmed; Papageorgiou, Maria; Deshmukh, Harshal; Madden, Leigh A.; Rigby, Alan; Kilpatrick, Eric S.; Atkin, Stephen L.; Sathyapalan, Thozhukat
Abstract : Aims: To assess whether endothelial microparticles (EMPs), novel surrogate markers of endothelial injury and dysfunction, are differentially produced in response to acute insulin‐induced hypoglycaemia in adults with and without type 2 diabetes. Materials and methods: A prospective, parallel study was conducted in individuals with type 2 diabetes (n = 23) and controls (n = 22). Hypoglycaemia (<2.2 mmoL/L: <40 mg/dL) was achieved by intravenous infusion of soluble insulin. Blood samples were collected at baseline and at 0, 30, 60, 120, 240 minutes and 24 hours after hypoglycaemia and analysed for CD31 + (platelet endothelial cell adhesion molecule‐1), CD54 + (intercellular adhesion molecule 1), CD62‐E + (E‐selectin), CD105 + (endoglin), CD106 + (vascular cell adhesion molecule 1) and CD142 + (tissue factor) EMPs by flow cytometry. The peak elevations (% rise from 0 minutes after hypoglycaemia) in EMP within 240 minutes after insulin‐induced hypoglycaemia were modelled using a regression model, with adjustment for relevant covariates. All EMPs were expressed as percentage from 0 minutes hypoglycaemia for each time point and total areas under the curve (AUC0min–24h ) were calculated. Results: Following insulin‐induced hypoglycaemia, levels of circulating EMPs were maximal at 240 minutes ( P < 0.001) and returned to baseline values within 24 hours for both groups. The peak elevations (% rise from 0 minutes following hypoglycaemia) seen in CD31 +, CD54 +, CD62‐E +, CD105 + and CD142 + EMPs within 240 minutes were associated with diabetes status after adjustments for all relevant covariates. Individuals with type 2 diabetes showed increased CD31 + EMPs AUC0min–24h ( P = 0.014) and CD105 + EMPs AUC0min–24h ( P = 0.006) compared with controls, but there were no differences for CD54 + ( P = 0.91), CD62‐E + ( P = 0.14), CD106 + ( P = 0.36) or CD142 + ( P = 0.77) EMPs AUC0min–24h . Conclusions: The associations between peak elevations within 240 minutes after insulin‐induced hypoglycaemia for CD31 +, CD54 +, CD62‐E +, CD105 + and CD142 + and diabetes status indicate that the assessment of a panel of EMPs within this timeframe would identify a hypoglycaemic event in this population. The greater overall responses over time (AUCs) for apoptosis‐induced CD31 + and CD105 + EMPs suggest that hypoglycaemia exerts greater endothelial stress in type 2 diabetes.